2012
DOI: 10.1111/tid.12008
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Rhodococcus equi infection in a renal transplant patient: case report and review of the literature

Abstract: Rhodococcus equi is a pathogen that mainly causes infection in immunocompromised hosts. We report a case of relapsing R. equi pulmonary infection in a 57-year-old male renal transplant recipient who was treated with 12 months of antibiotics, adjunctive surgery, and a reduction in his immunosuppression. He suffered from relapsing disease, treatment-related complications, and ultimately died of Pneumocystis pneumonia. Case reports in the literature portray a good cure rate for transplant-related R. equi infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…5 A recent review of the literature has reported a total of 41 cases of R. equi infection in solid-organ transplant patients, 24 of which occurred in kidney transplants, 7 in hearts, 3 in livers and 6 in others. 6 In contrast to the majority of cases in the literature, our patient did not express any pulmonary involvement, instead showing only soft tissue and subcutaneous multiple abscesses. In our case the blood cultures always remained negative and the R. equi was isolated to the abscess liquid specimens only.…”
Section: R Equi (Previously Known As Corynebacterium Equi)contrasting
confidence: 95%
“…5 A recent review of the literature has reported a total of 41 cases of R. equi infection in solid-organ transplant patients, 24 of which occurred in kidney transplants, 7 in hearts, 3 in livers and 6 in others. 6 In contrast to the majority of cases in the literature, our patient did not express any pulmonary involvement, instead showing only soft tissue and subcutaneous multiple abscesses. In our case the blood cultures always remained negative and the R. equi was isolated to the abscess liquid specimens only.…”
Section: R Equi (Previously Known As Corynebacterium Equi)contrasting
confidence: 95%
“…In a review of 2012, infection with Rhodococcus occurred mostly in immunosuppressed transplant recipients receiving a triple therapy including steroids, azathioprine or mycophenolate and a CNI. The delay between transplantation and Rhodococcus pneumonia was 3 years (3 months-19 years) [45]. Generally the disease tends to follow a subacute course with progressive cough, pleuritic chest pain, and fever often accompanied by cachexia, weight loss and fatigue.…”
Section: Rhodococcus Equimentioning
confidence: 99%
“…The bacteria can be isolated from blood cultures (25% of transplant recipients have a concomitant bacteremia). Culture of sputum is positive in only 20% and should be held for more than 48 h [45]. Often the diagnosis needs bronchoalveolar lavage or biopsy.…”
Section: Rhodococcus Equimentioning
confidence: 99%
“…Some species also have industrial properties such as bioremediation and bioactive secondary metabolites of medical or industrial interest (Menon, Gottlieb, Gallagher, & Cheong, 2012;Nacoulma, Vandeputte, De Lorenzi, Jaziri, & Duez, 2013;Peng, Yang, Jia, & Li, 2013). It had no insecticidal activity on P. prasina.…”
Section: Numbermentioning
confidence: 99%